Efforts of Arab and Chinese Ethnic Groups in Maintaining Their Cultural Identity in a Malay-Muslim Environment in Palembang - Muchtar, Aflatun; Ari, Anggi Wahyu; Zain, Zaki Faddad Syarif; Firdaus, Aristophan (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2024)
This study explores the strategies employed by the Arab and Chinese ethnic groups to preserve their cultural identity within the predominantly Malay-Muslim environment of Palembang. Challenging the common assumption that minority groups are inherently powerless compared to the majority, this research reveals that both the Arab and Chinese communities possess significant influence in the socio-cultural landscape of Palembang. Employing a qualitative approach, with data collected through in-depth interviews, participant observation, and document analysis, the study examines how these communities navigate cultural assimilation pressures while maintaining distinct ethnic traditions. The findings indicate that both groups have successfully leveraged their social capital—Arabs through religion and Chinese through economic activities—to sustain their cultural identities and exert influence over the majority Malay population. Notably, this influence is reflected in the organization of significant social rituals, such as the Cap Go Meh Ritual by the Chinese and Ziarah Kubro by the Arabs. The study concludes that inter-ethnic adaptation in Palembang involves not only maintaining harmony but also contestation and negotiation among different groups. This dynamic interaction underscores the complexity of multiculturalism, where harmony is maintained through a pragmatic approach to mutual dependence. The implications of this research extend to policymakers and cultural organizations aiming to support ethnic diversity in a multicultural contex.